Energy saving control system application in lecture hall - Norhayanie, Roslan (2008)
Energy Saving Control System is created to reduce the power consumptions in University Malaysia Pahang (UMP). This system is designed to control the lighting system and air-conditioner. The quantity and the consumed of the lighting system and air conditioner can cause a lot of electrical energy wasted everyday. We all know sometimes lecturers or students forget to switch off the lighting system and air-conditioner before leaving the room. This system can control 8 units of lightning system and 6 unit of air conditioner. This project uses the Passive Infrared Sensor (PIR sensor) to detect the body heat and the movements of humans. The PIR sensor will give signal to hardware. The hardware of this project is PIC18F4620 and RS232 communication module to interface with Visual Basic (VB). When PIC get signal from the sensor, so lighting system and air-conditioner will turn OFF automatically after a delay time off 10 minutes. Within 10 minutes time frames, if the sensor detects human movement or heat in the area, the control system will reset its program not turn OFF the lighting system or air-conditioner system.